A inviabilidade do uso das Tecnologias da Informação e Comunicação no contexto escolar: o que contam os professores de matemática? - Oliveira, Franciele Taís de [UNESP] (2014)
This research aimed to investigate if the mathematics teachers are using the Information and Communication Technologies (ICT) as well as pointing how they make this use and/or the reasons of the nonuse. Whereas the focus of this research is guided to obtain an understanding of the subjective aspects of a particular social group, we chose a qualitative study approach. For the production of the data, we visited 19 elementary state public schools in the city of Bauru, and methodological procedures like questionnaires and interviews were used. Questionnaires were administered to 54 teachers of mathematics. And the interviews were conducted with six coordinators of the schools, the coordinator of the Programa Acessa Escola and the coordinator teacher of the pedagogic core (PCNP) of the Board of Education of Bauru, the latter two performed after the visits in schools in order to clarify and deepen the issues raised by teachers and coordinators. With systematically organized data, we initiated an analysis movement, in which the following categories emerged: the infrastructure of computer labs; teacher training; and conditions of teachers' work. Categories were discussed using the literature and formed what we call a network of meanings, understood in this context as the wires interconnecting the speeches of the participants involved with our inquiries while researchers. From the discussions, we infer that the scenario is bleak, especially regarding the physical structure of the computer labs. Few teachers use the ICT in their lessons, and when they use, it‟s only in the sense of inclusion, not integrating the computer into their pedagogic practice. Moreover, most of them do not feel prepared to use them in their classes, and this factor, coupled with the structural issue is reinforced by the fact that many of them use it in everyday life. Another factor influencing the non-use of ICT in the school environment concerns the precarious conditions...